SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PELANGGAN TERBAIK MENGGUNAKAN METODE WEIGHTED PRODUCT - Victor Marudut Mulia Siregar; Sahat Sonang; Erikson Damanik (Politeknik Bisnis Indonesia, 2021)
This study aims to overcome the problem of selecting the best customer at Pematangsiantar Subur Graphic Printing. For the smooth running of the printing business, Subur Graphics maintains good relations with consumers by giving rewards to the best customers. In determining the best customer for graphic fertile printing, it is still done manually. To help overcome the problem of selecting the best customer, a decision support system is designed. Web-based decision support system built using the Weighted Product method. This decision support system uses criteria consisting of total shopping, payment method, length of subscription, payment status and total visits. The result of this research is a web-based decision support system with an output consisting of recommendations for the three best customers, namely the first best alternative Pd_Pphn with a vector value of V 0.085, the second best alternative GPIB Maranatha with a vector value of V 0.080, and the third best alternative SPTI_Ib_Mrni with a vector value of V 0.077. With a decision support system for determining the best customer using the weighted product method, Subur Graphic Printing can easily select the best customer.